Trigonometric Identity

Geometry Level 2

Simplify tan ( A + π 2 ) . \tan\left(A + \frac{\pi}{2}\right).

cot A -\cot A cos A \cos A sin A \sin A tan A -\tan A

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Ilya Andreev
Aug 16, 2014

tan ( A + π 2 ) = sin ( A + π 2 ) cos ( A + π 2 ) = cos ( A ) sin ( A ) = cot ( A ) . \tan(A+\frac{\pi}{2})=\frac{\sin(A+\frac{\pi}{2})}{\cos(A+\frac{\pi}{2})}=\frac{\cos(A)}{-\sin(A)} =-\cot(A).

that's right

Karim Shaféiq - 6 years, 9 months ago
Rakshit Pandey
Aug 13, 2014

tan ( A + B ) = tan A + tan B 1 ( tan A tan b ) \tan (A+B)=\frac{\tan A + \tan B}{1-(\tan A \tan b)}
In this case, B = π 2 B=\frac {\pi}{2} ,
so,
tan [ A + π 2 ] = tan A + t a n π 2 1 tan A tan π 2 \tan [A+\frac {\pi}{2}]=\frac {\tan A + tan \frac{\pi}{2}}{1- \tan A \tan \frac{\pi}{2}}
Dividing both numerator and denominator on RHS by ( tan π 2 \tan \frac{\pi}{2} ),
tan [ A + π 2 ] = tan A tan π 2 + 1 1 tan π 2 tan A \Rightarrow \tan [A+\frac {\pi}{2}]= \frac {\frac{\tan A}{\tan \frac{\pi}{2}}+1}{\frac {1}{\tan \frac{\pi}{2}} - \tan A}
The reason behind doing this is that the value of the trigonometric function tan \tan at π 2 \frac{\pi}{2} approaches \infty , which would render the problem unsolvable. So, we divided both numerator and denominator by tan π 2 \tan \frac{\pi}{2} , so that the problem can become solvable.
Now,
tan [ A + π 2 ] = tan A + 1 1 tan A \Rightarrow \tan [A+\frac {\pi}{2}]=\frac {\frac{\tan A}{\infty}+1}{\frac {1}{\infty} - \tan A}
tan [ A + π 2 ] = 0 + 1 0 tan A \Rightarrow \tan [A+\frac {\pi}{2}]=\frac {0+1}{0 - \tan A}
tan [ A + π 2 ] = 1 tan A \Rightarrow \tan [A+\frac {\pi}{2}]=\frac {1}{- \tan A}
tan [ A + π 2 ] = cot A \Rightarrow \tan [A+\frac {\pi}{2}]=-\cot A
Hence, answer is cot A \boxed {-\cot A} .


Pavan Rao
Aug 9, 2014

As Tan(A +pi/2) lies in 2nd quadrant, tan changes to cot and as tan is -ve in 2nd quadrant, the answer is -cotA

tan ( A + π 2 ) = cot ( π 2 ( A + π 2 ) ) = cot ( A ) = \tan (A + \frac{\pi}{2}) = \cot (\frac{\pi}{2} - (A + \frac{\pi}{2})) = \cot ( - A)= = cos ( A ) sin ( A ) = cos ( A ) sin ( A ) = cot ( A ) = \frac{\cos ( - A)}{\sin ( -A)} = \frac{\cos (A)}{- \sin(A)} = - \cot (A)

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...